2022
DOI: 10.3390/ijms23073753
|View full text |Cite
|
Sign up to set email alerts
|

New and Emerging Targeted Therapies for Hidradenitis Suppurativa

Abstract: Hidradenitis suppurativa (HS) is a chronic, recurrent, inflammatory skin disease deriving from the hair follicles. The formation of inflammatory nodules, abscesses, fistulas, and sinus tracts is characterized by a large inflow of key pro-inflammatory mediators, such as IFN-γ, TNF-α, IL-1, IL-17, and IL-12/23. Adalimumab is currently the only Food and Drug Administration (FDA)- and European Medicines Agency (EMA)-approved biologic therapy for moderate to severe HS in adults and adolescents. However, the long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 156 publications
(250 reference statements)
0
14
0
1
Order By: Relevance
“…HS therapeutic options are based on disease severity and include a combination of topical and systemic therapies, including biologic drugs, surgical approach, as well as general measures and analgesics to reduce both pain and the burden of disease [ 33 ]. Topical application of clindamycin twice a day on the affected areas represents the mainstay treatment in the milder localized form of HS, whereas systemic antibiotic therapies with tetracyclines, clindamycin, and/or rifampicin in different regimens is often required to control the disease and reduce the flares in non-responders to topical therapy and moderate HS [ 26 ]; acitretin and dapsone could be employed as an alternative to, or in combination with, antibiotic therapy in mild-to-moderate HS [ 26 ].…”
Section: Therapeutic Strategies For Hsmentioning
confidence: 99%
See 2 more Smart Citations
“…HS therapeutic options are based on disease severity and include a combination of topical and systemic therapies, including biologic drugs, surgical approach, as well as general measures and analgesics to reduce both pain and the burden of disease [ 33 ]. Topical application of clindamycin twice a day on the affected areas represents the mainstay treatment in the milder localized form of HS, whereas systemic antibiotic therapies with tetracyclines, clindamycin, and/or rifampicin in different regimens is often required to control the disease and reduce the flares in non-responders to topical therapy and moderate HS [ 26 ]; acitretin and dapsone could be employed as an alternative to, or in combination with, antibiotic therapy in mild-to-moderate HS [ 26 ].…”
Section: Therapeutic Strategies For Hsmentioning
confidence: 99%
“…Topical application of clindamycin twice a day on the affected areas represents the mainstay treatment in the milder localized form of HS, whereas systemic antibiotic therapies with tetracyclines, clindamycin, and/or rifampicin in different regimens is often required to control the disease and reduce the flares in non-responders to topical therapy and moderate HS [ 26 ]; acitretin and dapsone could be employed as an alternative to, or in combination with, antibiotic therapy in mild-to-moderate HS [ 26 ]. Adalimumab, an antagonist of TNF (Tumor Necrosis Factor)-α, is the only approved biologic drug for moderate-to-severe HS, with a significant improvement ranging from 41.8% to 77% of treated patients, as shown in clinical trials and real-life observational studies [ 33 ]; the evidence of a “window of opportunity” supports the early use of adalimumab in HS to ensure better clinical response [ 34 ]. Surgical treatments (e.g., deroofing, incision and draining, local excision of the lesions) are taken into account in the most severe stage of HS with extensive and long-standing sinus tracts/fistulae formation or in treatment-refractory disease [ 35 ].…”
Section: Therapeutic Strategies For Hsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adalimumab, a fully human, IgG1 monoclonal antibody specific for TNFα, is currently the only biologic therapy approved for the treatment of moderate-to-severe HS in adults and adolescent patients ≥12 years ( Table 4 ) [ 20 , 22 , 112 ]. In two phase III multicenter, double-blind, placebo-controlled studies (PIONEER I and PIONEER II) adalimumab showed a significant effectivity compared to placebo with HiSCR rates of 41.8% and 58.9% (vs. 26.0% and 27.6% in placebo groups), respectively [ 113 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Obecnie prowadzone są również badania nad zastosowaniem Avacopan w leczeniu trądziku odwróconego 12 oraz roli terapii celowanej w receptor C5a w leczeniu immunosupresji w posocznicy. 13 Ponadto Avacopan może w przyszłości posłużyć jako inhibitor granulocytów w leczeniu pacjentów z toczniem rumieniowatym układowym.…”
Section: Potencjalne Zastosowanieunclassified